(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Wound is breaking in the continuity of any bodily tissue due to external action, by cut, bruise, or hematoma. From the time of Vedas wound and its management is one of the challenging task with which health science is dealing. A chronic wound is the wound that does not heal in an orderly set of stages and in a predictable amount of time or wounds that do not heal within three months are often considered chronic. There are many factors involve in healing of any wound. All factors should present at correct time to heal any wound but absence of any factors leads to delayed wound healing or non-healing wound. Modern science has explained in wound healing it involves Multiple cell actions and extracellular matrix and soluble mediators such as growth factors and cytokines. According to science wound dressings are conventionally only applied to shield the wound from external contamination so they don’t have any involvement in wound healing. In advanced era technology related to wound healing is developing rapidly. In Ayurveda Acharya Sushruta described various therapies for wound management i.e., Shashti Upakrama. One of them is Jalaukavacharan, leech application on the wound site. As leech contains various chemicals in their saliva, this chemical helps in reducing the blockage in the capillaries and improves micro- circulation. Here is a case study of patient suffering from non-healing wound treated with leech application.